Painless scaling rewiring your existing stacks for scalability - Werther, Ben.; Safari eBooks; O'Reilly strata making data work conference (2011 : (dollar)c Santa Clara, Calif.) ([Sebastopol, Calif.?] : O'Reilly Media, 2011)
"If you are a leading enterprise or web company, then two things are almost certainly true. Data is the lifeblood of your business. And you face an ever-increasing need to scale your applications and data services."--Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, CA.
Keywords: Distributed databases; Database management -- Computer programs; Apache Cassandra (Computer system); Electronic books